The role of XBRL adoption on enhancing transparency of information disclosure: A case study of Jordanian financial companies - Hani Alkayed; Saad Zighan; Majed Qabajeh; Mohammad I. Almaharmeh (Cogent Business & Management, 2023)
The current study investigates the role of eXtensible Business Reporting Language (XBRL) on the transparency and efficiency of information disclosure in Jordanian financial companies. Based on a sample of 124 respondents, including accountants, academics, and auditors with a background in XBRL. We find that there is a significant positive impact of adopting XBRL on improving information transparency and efficiency of Jordanian financial companies. XBRL reporting leads to better, more relevant, reliable, and transparent financial information, simplifying preparing group financial statements. XBRL is more critical for sustainability reporting than financial reporting because sustainability reporting is primarily optional. XBRL holds more potential for promoting corporate social and environmental sustainability performance reporting. The study heightened the importance of using the XBRL framework in preparing their financial reports to increase the level of confidence by external parties in the management system of these companies. While this research contributes to the existing knowledge base, it also underlines the need for further exploration into this field. The implications for regulators and financial companies are clear, and addressing the identified limitations can refine future research efforts. XBRL continues to be a vital tool in financial reporting, offering opportunities for growth, transparency, and efficiency in Jordan and beyond.
Keywords: 650; financial reporting; financial sector; information disclosure; information transparency; XBRL